Stakeholder Orientation, Product Market Competition, and the Cost of Equity - Chen, Zhihong; Shen, Sichen; Zou, Hong (The Review of Corporate Finance Studies, 2026)
By examining required rates of return, we study how shareholders perceive stronger stakeholder orientation arising under the adoption of constituency statutes. Constituency statutes decrease (increase) the cost of equity for firms operating in high- (low-) competition industries. For firms in high-competition industries, constituency statutes increase future cash flows and performance resilience to negative industry downturns, suggesting that constituency statutes facilitate CSR activities for product differentiation in competitive industries. In contrast, for firms in low-competition industries, constituency statutes reduce future cash flows and increase tail risks, suggesting that constituency statutes shield managerial agency problems from discipline.